Determinasi Teknologi Komunikasi dan Adaptasi Media Pembelajaran di Masa Pandemi COVID-19 - Mellisa Fransisca; Rizki Briandana (UMSU, 2022)
Ukrida has implemented an online learning system starting March 23, 2020 as an effort to control the spread of the Covid-19 virus. Technological changes in the learning system from face-to-face to online